A new family of marx generators based on commutation circuits - Zabihi, S.; zare, F.; Ledwich, G.; Ghosh, Arindam; Akiyama, H. (IEEE Dielectrics and Electrical Insulation Society, 2011)
This paper presents a novel topology for the generation of high voltage pulses that uses both slow and fast solid-state power switches. This topology includes diode-capacitor units in parallel with commutation circuits connected to a positive buck-boost converter. This enables the generation of a range of high output voltages with a given number of capacitors. The advantages of this topology are the use of slow switches and a reduced number of diodes in comparison with conventional Marx generator.Simulations performed for single and repetitive pulse generation and experimental tests of a prototype hardware verify the proposed topology.